Knowledge of Mothers Towards Infant’s Oral Healthcare in Lahore - Talha Asif, Muhammad Waqas Rashid, Shamima Abdullah, Sibgha Afzal, Fazeela Zahid, Mehvish Saleem (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective of current study is to assess the knowledge of mothers regarding oral health maintenance of infants. Method: This descriptive crossectional study was conducted in a tertiary hospital of Lahore after getting the approval from intuitional ethical committee. The sample size of the current study was 238 mothers with an age ranges between 21years to 35years. Data was collected using convenient sample technique. For data collection, a questionnaire was adopted from a previous study conducted in India on the similar topic.9 SPSS version 25.0 was used to analyzed data. For age of mother and child, mean and standard deviation were calculated whereas for educational level and other questions based on knowledge of maintaining oral health among infants, frequencies and percentages were calculated. Results: Majority of mothers 178(74.79%) reported that transmission of cariogenic bacteria is not possible from mother to infant. Majority of mothers 189(79.41%) reported that bottle feeding during night is not the major reason of dental caries among infants. Majority of mothers 160(67.21%) reported that regular and persistent nighttime breast feeding is not a cause of caries development among infants. Majority of mothers 130(54.62%) reported that they are not sure about importance of oral health maintenance for infants’ general health Conclusion: In conclusion, there is a need to plan an awareness program to educate mothers about the importance of maintaining oral health status of infants to avoid dental caries. Keywords: Dental Caries, Oral Health, Cariogenic bacteria